UPAYA PENINGKATAN PENDAPATAN PETANI PADI MELALUI PROGRAM BANTUAN BIBIT DAN PUPUK PADA DINAS PERTANIAN KABUPATEN BONE BOLANGO - Machmud, Joice; Mokodompit, Nur Eng; Tangahu, Wilda (Universitas Muhammadiyah Gorontalo, 2024)
The purpose of this study is to determine the efforts to increase the income of rice farmers through the assistance of seeds and fertilizers in Bone Bolango Regency. This study used a qualitative approach and the research instrument was interviews with predetermined informants.The results of the study concluded that efforts to increase the income of rice farmers through seed and fertilizer assistance programs have been able to increase the income of rice farmers in Bone Bolango Regency. The increase in the income of rice farmers was due to the reduced cost of production factors, especially the purchase of seeds and fertilizers by farmers as well as the use of superior seeds and the use of fertilizers in accordance with the actual standard of fertilizer application. That is done 3 times until the harvest arrives. In addition, the provision of seeds and fertilizers distributed by the Department of Agriculture coincided with the prevailing planting season in Bone Bolango Regency. The results also showed that the provision of seed and fertilizer assistance to rice farmers was able to increase rice production in Bone Bolango Regency to reach 120,361 tons by 2020 with the achievement of recipients of assistance to 5,706 farmers and the area of rice fields reaching 3100 Ha. In addition, farmers' rice production per hectare reached 6-7 tons, which previously only ranged from 5 to 5.4 tons per hectare.